Factors affecting the mathematics performance of mdab students - Mohd Basir, Nora; Jangga, Rohani (2012)
MDAB is a program with the objective of helping Bumiputra youths, who aspire to become a Diploma holder at least but are less fortunate in terms of academic qualifications and thus are not qualified to apply for a Diploma Program. For the MDAB program, all students must complete a 4 month course successfully before they can proceed to the next level which is the diploma level. Besides offering them a place in UiTM branch campuses, they are also given a monthly allowance of RM400. However, for the first batch of students, 52% of the students have failed to further their studies to the diploma level and Mathematics has been identified as the subject where most students failed. From the financial point of view, this high percentage of failure indicated that thousands of ringgit has been wasted on the students that failed their final examination. For that reason, the objective of this research is to identify the underlying factors that are associated with the performance of the students in Mathematics and to identify the level of influences of these factors towards their performance in this subject. The study is a cross sectional study and the population consist of all students in UiTM Segamat from the December 2010 to March 2011 intake only. This is to ensure the maximum response rate from the respondents. Questionnaires were distributed to the students during the final weeks before examination week started. The data were analyzed using tabular analysis techniques. Besides that, Chi-square Test and Factor Analysis were used in determining the most influential factor that affect Mathematics performance and also the level of influences of these factors. From the findings, it can be concluded that various types of academic motivation are related to individual differences in that pre diploma students have different reasons for pursuing this program. Knowing that students require different incentives for getting thorugh university, it is possible for lecturers, parents and the students themselves to come up with teaching, planning and learning strategies that are suitable to each student's needs. Results for Mathematics during the SPM examination have a significant effect on the performance of MDAB students when they sat for their final exams in UiTM. It has thus been proven that students who did well in Mathematics during their SPM will achieve similar results for their pre diploma examinations.